Dynamic credit constraints: Theory and evidence from credit lines - Niklas Amberg; Tor Jacobson; Vincenzo Quadrini; Anna Rogantini Picco (Sveriges Riksbank, 2023)
We use a comprehensive Swedish credit register to document that firms throughout the size distribution have access to fairly large and reasonably priced credit lines, but borrow relatively little from them. We rationalize this using a theoretical framework in which the expected cost of financial distress increases with current borrowing and lower credit-line utilization reflects tighter 'dynamic' credit constraints. Consistently with the predictions of the model, the data shows that there is a negative relation between firm-level uncertainty and credit-line utilization. We also find that firms increase borrowing in response to credit-limit increases, even when their current debt is far from the limit.
Keywords: D22; E44; G21; G32; 330; Credit constraints; banks; uncertainty; credit lines; precautionary behavior